The Use of The Gapuro System as a Radio Frequency Identification (RFID) Tool with the Technology Acceptance Model (TAM) Method on Employee Productivity at PT. Epson Batam - Rahman, Fuad Arif; Tiara Putri, Muti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This paper examines the impact of the Gapuro system, which is used as a Radio Frequency Identification tool, on employee productivity at PT Epson Batam through the Technology Acceptance Model (TAM). The TAM model assesses how perceived benefits, perceived ease of use, attitudes towards use, behavioral intentions to utilize, and actual systems related to the Gapuro system affect employee productivity. The writing design uses a quantitative methodology with a descriptive framework. The writing sample was obtained using a non-probability methodology using the purposive sampling method, with 102 respondents representing the entire workforce of the IK-Production molding department of PT. Epson Batam. The data collection method uses a questionnaire. In contrast, the data processing strategy involves instrument testing, correlation analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results show that perceived ease of use and intention to use the system significantly affect employee productivity. Meanwhile, perceived usefulness, attitudes towards use, and actual use show no significant direct effect on productivity. This writing has an important impact on companies in increasing the effectiveness of technology implementation and developing better technology training and adoption strategies.